LEGAL FRAMEWORK AND CREDITOR RIGHTS IN BANKRUPTCY: ANALYZING PROPERTY COLLATERAL PROTECTION - Zuroidah, Zakiyah Nur; Prasetyo, Dr. Dossy Iskandar (jfpublisher, 2024)
Bankruptcy is a legal process to settle the debts of debtors who are unable to pay their debts. In this process, the rights of creditors holding collateral may be affected. Uncertainty occurs because creditors do not control whether they can execute the collateral themselves or have to wait for the curator’s decision. In bankruptcy, property secured creditors face substantial risk of recovering their receivables. Property collateral, such as land and buildings, is often the main collateral to protect creditors' rights. However, complex insolvency procedures and lack of legal clarity often put creditors in a vulnerable position. This research analyzes the existing legal framework and how it protects the rights of secured creditors. Clearer and stronger protections are needed to create legal certainty and maintain financial system stability. This research uses a normative legal approach with statutory and conceptual methods. The results indicated that creditors holding collateral have the right to execute collateral through parate executie (direct execution), but are limited by the stay provisions in the Bankruptcy and PKPU Law. The curator can also execute the collateral with the approval of the supervisory judge and creditors. Both creditors and the curator can auction the collateral. In bankruptcy, creditors holding collateral have the priority right to execute the collateral. If the proceeds from the execution are not enough to pay off the debt, the creditor can submit the remaining bills as a concurrent creditor to the curator.